Baseline Quality of Life of Physical Function Is Highly Relevant for Overall Survival in Advanced Rectal Cancer - Fitz, Tim; Sörgel, Christopher; Rutzner, Sandra; Hecht, Markus; Fietkau, Rainer; Distel, Luitpold (Healthcare, 2022)
In advanced rectal cancer, neoadjuvant radiochemotherapy and total mesorectal excision lead to long overall survival. The quality of life (QOL) of the patients is clearly related to the prognosis. Our question was whether the prognosis can be represented with only one question or one score from the QOL questionnaires. 360 consecutively recruited patients diagnosed with advanced rectal cancer were questioned during radiochemotherapy and a follow-up of 8 years. The questionnaires QLQ-C30 and QLQ-CR38 were used; 10 functional and 17 symptom scores were calculated. The functional score “physical function” and the symptom scores “fatigue”, “nausea and vomiting”, “pain” and “appetite loss” were highly prognostic (p < 0.001) for overall survival. “Physical function” was highly prognostic at all time points up to 1 year after starting therapy (p ≤ 0.001). The baseline “physical function” score divided the cohort into a favorable group with an 8-year overall survival rate of 70.4% versus an unfavorable group with 47.5%. In the multivariable analysis, baseline “physical function”, age and distant metastases were independent predictors of overall survival. The score “physical function” is a powerful unrelated risk factor for overall survival in patients with rectal cancer. Future analyses should study whether increased “physical function” after diagnosis could improve survival.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Age; Physical function; Quality of life; Radiochemotherapy; Rectal cancer

Impact of COVID-19 on Quality of Life in Long-Term Advanced Rectal Cancer Survivors - Blasko, Daniel; Schweizer, Claudia; Fitz, Tim; Schröter, Christoph; Sörgel, Christopher; Kallies, Annett; Fietkau, Rainer; Distel, Luitpold (Healthcare, 2023)
Colorectal cancer remains one of the most commonly diagnosed cancers. Advanced rectal cancer patients receive neoadjuvant radiochemotherapy as well as surgery and suffer from reduced health-related quality of life due to various side effects. We were interested in the role of the COVID-19 pandemic and how it affected those patients’ quality of life. A total of 489 advanced rectal cancer patients from the University Hospital Erlangen in Germany were surveyed between May 2010 and March 2022 and asked to fill out the EORTC QLQ-C30 and QLQ-CR38 questionnaires over eight different time points: at the beginning, during and after radiochemotherapy, right before surgery, and in yearly intervals after surgery for up to four years. Answers were converted to scores to compare the COVID-19 period to the time before March 2020, focusing on the follow-ups, the developments over time—including by sex and age—and the influence of the TNM cT-stage. Overall, a trend of impaired functional and symptom scores was found across all surveys with few significances (body image −10.6 percentage points (pp) after one year; defecation problems +13.5 pp, insomnia +10.2 pp and weight loss +9.8 pp after three years; defecation problems +11.3 pp after four years). cT4-stage patients lost significantly more weight than their cT1-3-stage counterparts (+10.7 to 13.7 pp). Further studies should be conducted to find possible causes and develop countermeasures for future major infectious diseases.
CRIS-Team Scopus Importer:2023-08-11
Keywords: COVID-19; pandemic; quality of life; radiochemotherapy; rectal cancer

Physical Fitness in Combination with Age is an overwhelming prognostic Factor in Patients with advanced Rectal Cancer - Fitz, Tim; Sörgel, Christopher; Rutzner, Sandra; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Substantial Impairment of Quality of Life during COVID-19 Pandemic in Patients with Advanced Rectal Cancer - Dennison, Irene; Schweizer, Claudia; Fitz, Tim; Blasko, Daniel; Sörgel, Christopher; Kallies, Annett; Schmidt, Linda; Fietkau, Rainer; Distel, Luitpold (Healthcare, 2022)
The aim of this study was to analyze the quality of life of patients with advanced rectal cancer before and during the COVID-19 pandemic and to determine whether the pandemic affected patients' quality of life. The study included 389 patients and was performed from May 2010 to June 2021. The fifteen months from March 2020 to June 2021 were categorized as the COVID-19 period. Patients were surveyed using the QLQ-C30 and QLQ-CR38 questionnaires. The questionnaires were used at different phases of radiochemotherapy: prior to RCT (day 1), during RCT (day 14), at the end of RCT (day 35), and prior to mesorectal surgery (day 70). Scores were formed from the questions. In addition, scores were analyzed for different age groups (64) and sexes (female and male). Overall, patients reported lower functional scores and higher symptom scores during the pandemic than before the pandemic. Although it had been expected that older and younger patients would differ clearly, there were only minor differences. The comparison between the two sexes showed very different scores, with female patients having lower functional scores and higher symptom scores than male patients before and especially during COVID-19. In conclusion, age does not play a major role in quality of life, but sex does play an important role in perception of functioning and symptoms. COVID-19 also had a major impact on patients' lives, as it was a very isolating and stressful time for everyone, especially cancer patients, which was reflected in worsening scores.
CRIS-Team WoS Importer:2022-09-09